(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To establish a relationship of diabetic retinopathy with the presence of lesions of other target organs, disease severity and the requirement for insulin therapy in patients with type 2 diabetes mellitus, and to determine the most significant prognostic markers. Material and Methods: We examined 270 patients (270 eyes) with type 2 diabetes mellitus. They were divided into the diabetic retinopathy group and no-diabetic retinopathy group. The status of diabetic target organs was determined as per endocrinologist’s, cardiologist’s, nephrologist’s, neurologist’s and vascular surgeon’s conclusions. Statistica v6.1 (Statsoft, Tulsa, OK) software was used for statistical analysis. The level of significance р < 0.05 was assumed. Results: Diabetic retinopathy positively correlated with severe diabetes (r = 0.383, p < 0.001), insulin therapy requirement (r = 0.389, p < 0.001), diabetic nephropathy (r = 0.350, p < 0.001), chronic kidney failure (r = 0.390, p < 0.001), and lower-extremity angiopathy (r = 0.312, p < 0.001). In addition, the risk of diabetic retinopathy was high in patients on insulin therapy (odds ratio (OR) 6.1; 95 % СІ 3.40-10.93), patients with diabetic nephropathy (OR 17.34; 95 % СІ 4.94-60.83), chronic kidney failure (OR 6.88; 95 % СІ 3.66-12.94), lower-extremity angiopathy (OR 19.15; 95 % СІ 4.24-86.45), coronary heart disease (OR 2.4; 95 % СІ 1.21-4.76) and essential hypertension (OR 4.29; 95 % СІ 1.22-15.10). The risk of diabetic retinopathy was higher in patients with severe diabetes (OR 5.79, 95% CI 3.26-10.26) as compared to patients with mild to moderate diabetes. Conclusion: The positive associations of diabetic retinopathy with chronic kidney failure, diabetic nephropathy and lower-extremity angiopathy were stronger than the positive associations with other diabetic target organs. In addition, there was a moderate positive correlation of diabetic retinopathy with severe diabetes and insulin therapy requirement. The association of diabetic retinopathy with acute coronary and cerebral events was not significant.